ANALISA BISNIS EKONOMI KREATIF SUB SEKTOR KULINER UNTUK MENINGKATKAN KEPATUHAN WAJIB PAJAK ( Studi Kasus Pada Pelaku Ekonomi Kreatif di Kabupaten Malang ) - Bunga Vergia Rakhmah; Jeni Susyanti; Muhammad Agus Salim (E-JRM : Elektronik Jurnal Riset Manajemen, 2019)
ABTRACKThe purpose of this study was to analyze creative economic entrepreneurs in the culinary sub-sector in order to meet taxpayer compliance. The population is 50 culinary sub-sector creative economic entrepreneurs in Malang Regency. Because the population is relatively small, all populations are sampled. The sampling technique uses quantitative methods. The technique sampling uses quantitative methods. The data testing techniques used in this study include description test, normality test, classic assumption test, simple linear regression analysis, and testing the research hypothesis. The results of the analysis show that the culinary sub-sector creative economic business significantly affects taxpayer compliance with a t-count value of 4,370 and a significance value of 0,000 or 58.9%. Keywords: creative economic, culinary, taxpayer compliance